Rifts and deficits – lessons of the historical model of Hungary’s administrative justice - András Patyi (Institutiones Administrationis, 2021)
The establishment of independent administrative courts at the beginning of 2020 was repealed by Parliament, including the underlying constitutional provisions, it is still the ordinary courts (including the Supreme Court – Curia) that handle legal disputes of administrative nature. The article introduces the historical model of Hungary’s administrative justice (between 1884 and 1949), emphasising its limited use as an example for the current challenges. We cannot speak of continuous historical evolution. It is more accurate to talk about fragments or fragmented short time periods. The changes and reform plans from 27 February 1884 (the “birthday” of Hungary’s administrative justice) are analysed in the article. The different proposals from the jurisprudence and the only administrative court itself are explained in detail. The role similar to the constitutional courts aspired by the administrative court is also examined. An important declaration from all of the judges of the administrative court (in 1947), according to which the court would not apply legal regulations violating a person’s natural and inalienable rights listed in the Act I of 1946, is also analysed.